2016
DOI: 10.1002/jcp.25684
|View full text |Cite
|
Sign up to set email alerts
|

Lgr4 Expression in Osteoblastic Cells Is Suppressed by Hydrogen Peroxide Treatment

Abstract: LGR4 is expressed in bone and has been shown to be involved in bone metabolism. Oxidative stress is one of the key issues in pathophysiology of osteoporosis. However, the link between Lgr4 and oxidative stress has not been known. Therefore, effects of hydrogen peroxide on Lgr4 expression in osteoblasts were examined. Hydrogen peroxide treatment suppressed the levels of Lgr4 mRNA expression in an osteoblastic cell line, MC3T3-E1. The suppressive effects were not obvious at 0.1 mM, while 1 mM hydrogen peroxide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…However, the correlation between LGR4 and oxidative stress remained unknown. Pawaputanon Na et al explored that the treatment of hydrogen peroxide decreased the expression of LGR4 in osteoblastic cells ( Pawaputanon Na Mahasarakham et al, 2017 ). Rspo1-LGR4 axis protected hepatocytes against acute injury by suppressing NF-κB-p65 via Wnt3a/β-catenin pathway ( Li Z. et al, 2019 ).…”
Section: The Role Of Lgr4 In Oxidative Stress Damagementioning
confidence: 99%
“…However, the correlation between LGR4 and oxidative stress remained unknown. Pawaputanon Na et al explored that the treatment of hydrogen peroxide decreased the expression of LGR4 in osteoblastic cells ( Pawaputanon Na Mahasarakham et al, 2017 ). Rspo1-LGR4 axis protected hepatocytes against acute injury by suppressing NF-κB-p65 via Wnt3a/β-catenin pathway ( Li Z. et al, 2019 ).…”
Section: The Role Of Lgr4 In Oxidative Stress Damagementioning
confidence: 99%
“…Another study used the MCT3-E1 cell line to show that RSPO2-LGR4 signaling not only induced osteogenesis but also inhibited osteoclastogenesis through the Wnt signaling pathway [78]. In osteoblastic cells, LGR4 expression is induced by the BMP protein during osteoblast differentiation and activation [79,80]. Opposing to this induction, Cong et al 2017 showed that microRNA-34c can inhibit LGR4 transcription, thus inducing osteoclast differentiation, regulating NF-κB and GSK3β signaling during that process [32].…”
Section: Bonementioning
confidence: 99%